How to reduce wastes and save materials - Mohd. Zulkifli Mohd. Ghazali, Tan Sri Prof. Ir. Dr., 1951-; Mohd. Azraai Kassim, 1958-; Leadership Seminar on Environmental and Urban Management (1993 : UTM, Sekudai)
10